Geochemical evaluation of black limestones in the Early Cretaceous platform carbonates of Gümüşhane (NE Turkey): An insight into petroleum source rock potential and palaeoenvironment conditions - Çiğdem Saydam Eker; Uğur Volkan Arı; Selçuk Alemdağ (The Depositional Record)
Abstract This study assesses the organic matter (OM) content, kerogen type, maturity, depositional environment conditions and sedimentation model of Early Cretaceous (Berriasian–Aptian) black limestones in NE Turkey using geochemical analyses, including Rock‐Eval/total organic carbon (TOC), gas chromatography–mass spectrometry, gas chromatography, major and trace elements and stable carbon isotope of OM measurements. The investigated black limestones' TOC, hydrogen index and potential yield values range from 0.07 to 2.91 wt%, 76 to 636 mg HC/g TOC and 0.15 to 11.17 mg HC/g rock, respectively. These results indicate that the examined limestones have variable source rock potential, ranging from low to high. Tmax values, calculated saturated biomarkers and aromatic components suggest that the OM contained in the black limestones varies between thermally immature and mature, consistent with the potential index values. The OM found in the black limestone contained kerogen varying between type I and III. It is a composition of marine and terrigenous OM, as shown by the δ13C isotope values, biomarker components and n‐alkane distributions and their parameters. This OM was deposited in a salinity water environment with marine–terrigenous (transitional) surroundings under oxic, suboxic to anoxic and arid–hot climate conditions. These findings provide critical insights for assessing the hydrocarbon potential of carbonate platforms in similar geological settings.